2015
DOI: 10.1055/s-0034-1380493
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidative Heterocyclization of Semicarbazones: An Efficient Approach for the Synthesis of 1,3,4-Oxadiazoles

Abstract: A highly efficient eosin Y catalyzed oxidative heterocyclization of semicarbazones was established under visible-light photoredox catalysis using CBr 4 as a bromine source. The protocol renders a rapid, mild, and efficient access to valuable 5-substituted 2-amino-1,3,4-oxadiazoles in an operationally simple way utilizing visible light and atmospheric oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…† Selective N-methylation of the quinuclidine N (N1) is achieved by treating Qn with MeI at room temperature, 28 giving MeQn + , whereas a reaction temperature of 100 C leads to Me 2 Qn 2+ by N-methylation of both N1 and the quinoline N (N2). 29,30 This selectivity follows the known basicity trend of N1 and N2. 21,31,32 Methylation at each site gives characteristic changes in 1 H NMR chemical shis ( Fig.…”
Section: Resultsmentioning
confidence: 53%
“…† Selective N-methylation of the quinuclidine N (N1) is achieved by treating Qn with MeI at room temperature, 28 giving MeQn + , whereas a reaction temperature of 100 C leads to Me 2 Qn 2+ by N-methylation of both N1 and the quinoline N (N2). 29,30 This selectivity follows the known basicity trend of N1 and N2. 21,31,32 Methylation at each site gives characteristic changes in 1 H NMR chemical shis ( Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Yadav et al reported the synthesis of 1,3,4-oxadiazoles from aldehyde semicarbazones, using CBr 4 , green LEDs and Eosin Y as the photocatalyst, at room temperature, in the presence of air (Scheme 18) [63]. …”
Section: Reviewmentioning
confidence: 99%
“…Selective N-methylation of the quinuclidine N (N1) is achieved by treating Qn with MeI at room temperature, 27 giving MeQn + , whereas a reaction temperature of 100 °C leads to Me2Qn 2+ by N-methylation of both N1 and the quinoline N (N2). 28,29 This selectivity follows the known basicity trend of N1 and N2. 20,30,31 Methylation at each site gives characteristic changes in 1 H NMR chemical shifts (Figs.…”
Section: Resultsmentioning
confidence: 54%